Building a new Afghanistan - Rotberg, Robert I.; World Peace Foundation (Cambridge, Mass. : World Peace Foundation ; Washington, D.C. : Brookings Institution Press, 2007)
"Discusses what Afghanistan and the international community should do to resolve dangerous issues and bolster a still fragile state. Offers a blueprint for moving toward greater democracy and prosperity while arguing that the future success of state building in Afghanistan depends on diversifying the economy and enhancing its economic status"--Provided by publisher.
Preface -- Map of Afghanistan -- Renewing the Afghan State / Robert I. Rotberg -- The legacy of war and the challenge of peace building / Ali A. Jalali -- Strengthening security in contemporary Afghanistan : coping with the Taliban / Hekmat Karzai -- Neither stable nor stationary : the politics of transition and recovery / Paula R. Newberg -- Rebuilding a robust Afghan economy / Alastair J. McKechnie -- Revitalizing Afghanistan's economy : the government's plan / Hedayat Amin Arsala -- Regional development in greater Central Asia : the Afghan pivot / S. Frederick Starr -- Responding to the opium dilemma / Cindy Fazey -- The place of the province in Afghanistan's subnational governance / Sarah Lister and Hamish Nixon.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Nation-building -- Afghanistan; Postwar reconstruction -- Afghanistan; Democratization -- Afghanistan; National security -- Afghanistan; Afghanistan -- Politics and government -- 2001-2021.; Reconstruction d'une nation -- Afghānistān.; Reconstruction d'après-guerre -- Afghānistān.; Démocratisation -- Afghānistān.; Sécurité nationale -- Afghānistān.; Afghānistān -- Politique et gouvernement -- 2001-2021.; HISTORY -- Military -- Afghan War (2001- ); POLITICAL SCIENCE -- Security (National & International); Democratization; Nation-building; National security; Politics and government; Postwar reconstruction; Afghanistan; Politieke situatie; Natievorming; Economische situatie; Afghanistan; Wiederaufbau; Politik; Afghanistan; gtt; 2001-; Narkotikapolitik -- Afghanistan; Narkotikahandel -- Afghanistan; Återuppbyggnad efter krig -- Afghanistan; Handelspolitik -- Afghanistan; Afghanistan -- politik och förvaltning.; Since 2001